The Influence of Computer Technology in Improving Learning Effectiveness at Imelda University Medan - Khairunnisa; Sari, Ika Yusnita; Rahmi, Elvika; Marpaung, Astrida N; Lumbanbatu, Maristella J (Jurnal Multimedia dan Teknologi Informasi (Jatilima), 2024)
This study aims to analyze the impact of computer technology usage in improving the effectiveness of learning at Universitas Imelda Medan. Based on data collected through surveys and interviews with lecturers and students, it was found that the use of computer technology significantly affects students' learning outcomes. The majority of respondents acknowledged that computer technology, such as the use of educational software, e-learning platforms, and multimedia applications, helps them better and more quickly understand the subject matter. Survey results showed that 85% of students feel more engaged and motivated to learn when using computer technology. Additionally, 75% of lecturers reported that computer technology allows them to teach more effectively, particularly in presenting complex material through visual and interactive means. However, challenges such as limited computer facilities and internet connection issues have become major obstacles in implementing this technology. The study concludes that while computer technology provides many benefits in enhancing learning effectiveness, improvements in facilities and training for lecturers are needed to maximize the use of technology in education